2017
DOI: 10.3892/br.2017.863
|View full text |Cite
|
Sign up to set email alerts
|

Role of amyloid β protein receptors in mediating synaptic plasticity

Abstract: Abstract. There are few diseases in modern biomedicine that have garnered as much scientific interest and public concern as Alzheimer's disease (AD). The amyloid hypothesis has become the dominant model of AD pathogenesis; however, the details of the hypothesis are changing over time. Recently, given the increasing recognition, subtle effects of amyloid β protein (Aβ) on synaptic efficacy may be critical to AD progression. Synaptic plasticity is the important neurochemical foundation of learning and memory. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…To date, oA β is acknowledged as the most synaptotoxic aggregate . oA β specifically interacts with a variety of receptors on the surface of both neuronal and glial cells, evoking signaling cascades that in turn modify the cellular profile of gene transcription/protein expression . In general, research on A β toxicity has focused mainly on its detrimental effects, culminating with significant declines in synaptic activity, neuronal metabolism, neurotrophic factors, as well as increased glial activation/inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, oA β is acknowledged as the most synaptotoxic aggregate . oA β specifically interacts with a variety of receptors on the surface of both neuronal and glial cells, evoking signaling cascades that in turn modify the cellular profile of gene transcription/protein expression . In general, research on A β toxicity has focused mainly on its detrimental effects, culminating with significant declines in synaptic activity, neuronal metabolism, neurotrophic factors, as well as increased glial activation/inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 oAβ specifically interacts with a variety of receptors on the surface of both neuronal and glial cells, evoking signaling cascades that in turn modify the cellular profile of gene transcription/protein expression. [6][7][8][9] In general, research on Aβ toxicity has focused mainly on its detrimental effects, culminating with significant declines in synaptic activity, neuronal metabolism, neurotrophic factors, as well as increased glial activation/inflammation. However, a more attentive look at the literature of the last two decades, points out the existence of a biphasic trend where all these reductions are preceded by transient paradoxical rises.…”
Section: Introductionmentioning
confidence: 99%
“…Aβ peptides then aggregate into extracellular insoluble senile plaques (Echeverria et al, 2004 ; Guardia-Laguarta et al, 2010 ; Ahyayauch et al, 2012 ). This Aβ accumulation leads to decreased neuronal health and stability, increased deterioration, synaptic depression (Venkitaramani et al, 2007 ; Palop and Mucke, 2010 ; Li et al, 2017 ), oxidative stress (Butterfield et al, 2013 ; Arimon et al, 2015 ; Cheignon et al, 2018 ), augmented neuronal dysfunctions and inflammation (Barage and Sonawane, 2015 ; Marottoli et al, 2017 ). These dysfunctions caused by Aβ aggregation, become worst upon the presence of HIV-1 (András and Toborek, 2013 ; Martínez-Bonet et al, 2018 ) and drugs of abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that the progressive loss of synapses is an important characteristic of AD. Synapses are the sites of memory storage in the nervous system and the mechanism by which information is transferred, suggesting a relationship between synaptic plasticity degeneration and cognitive decline in AD [ 6 , 7 ]. Long-term potentiation (LTP) has been widely used for evaluating synaptic plasticity both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%